2011
DOI: 10.1093/pcp/pcr186
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene's Role in Phosphate Starvation Signaling: More than Just a Root Growth Regulator

Abstract: Phosphate (Pi) is a common limiter of plant growth due to its low availability in most soils. Plants have evolved elaborate mechanisms for sensing Pi deficiency and for initiating adaptive responses to low Pi conditions. Pi signaling pathways are modulated by both local and long-distance, or systemic, sensing mechanisms. Local sensing of low Pi initiates major root developmental changes aimed at enhancing Pi acquisition, whereas systemic sensing governs pathways that modulate expression of numerous genes encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 111 publications
2
79
0
1
Order By: Relevance
“…Our finding that three primary transcripts in the Yang ethylene cycle have increased abundance in the PdCR, coupled with earlier findings that P i -stressed lupin roots produce increased ethylene (Gilbert et al, 2000), support an interpretation that P i deficiency increases ethylene production in roots. Ethylene is important in modifying root architecture, restricting primary root elongation, and promoting lateral root formation (Nagarajan and Smith, 2012). Our RNA-Seq data show that 17 members of the APETALA2/Ethylene Response Ethylene Binding (AP2_EREB) TF family are down-regulated in PdCR (Table III).…”
Section: P I Deficiency Modifies Root Metabolismmentioning
confidence: 81%
“…Our finding that three primary transcripts in the Yang ethylene cycle have increased abundance in the PdCR, coupled with earlier findings that P i -stressed lupin roots produce increased ethylene (Gilbert et al, 2000), support an interpretation that P i deficiency increases ethylene production in roots. Ethylene is important in modifying root architecture, restricting primary root elongation, and promoting lateral root formation (Nagarajan and Smith, 2012). Our RNA-Seq data show that 17 members of the APETALA2/Ethylene Response Ethylene Binding (AP2_EREB) TF family are down-regulated in PdCR (Table III).…”
Section: P I Deficiency Modifies Root Metabolismmentioning
confidence: 81%
“…Furthermore, these authors found that AtPT2 expression was significantly reduced in the Arabidopsis ethylene insensitive mutants in2-5 and etr1-1 under conditions of P deficiency [69]. In addition to AtPT2 (Pht1;4), the AtPht1;1 gene, which encodes another transporter responsible for acquiring P from soil, also increased its expression under ACC (1-aminocyclopropane-1-carboxylic acid) treatment and reduced it with Ag + , demonstrating that ethylene is involved in the regulation of the induction of both P transporters [69,97]. Similar results have been obtained with Medicago falcata L. plants: the induction caused by P deficiency in the expression of two P transporters (MfPT1 and MfPT5), as well as that of the gene coding for an acid root phosphatase (MfPAP1), was clearly inhibited by treatments with AVG (aminoethoxyvinylglycine) and with Cobalt, both inhibitors of ethylene synthesis [99].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 98%
“…Nowadays, however, there is evidence that ethylene also plays an important role in the regulation of physiological responses to P deficiency, as is the case with Fe deficiency [5,69,70,97,98]. Using the P transporter gene, AtPT2, as a marker gene to identify mutants with alterations in the regulation of responses to P deficiency, Lei et al [69] identified a mutant of Arabidopsis thaliana, hps2, which showed enhanced responses to P deficiency.…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 99%
See 1 more Smart Citation
“…, Borch et al (1999 showed the participation of ethylene in the regulation of P deficiency responses. Since then, evidence has been accumulating in support of a role for ethylene in the regulation of both Fe (Romera et al, 1999(Romera et al, , 2015Waters and Blevins, 2000;Lucena et al, 2006;Waters et al, 2007;García et al, 2010García et al, , 2011García et al, , 2013García et al, , 2014Yang et al, 2014) and P deficiency responses (Kim et al, 2008;Li et al, 2011;Nagarajan and Smith, 2012;Wang et al, 2012Wang et al, , 2014c.…”
mentioning
confidence: 99%